Implementation of optical character recognition (OCR) module on semiconductor etching tools for wafer tracking - Lai, Yeu Kwong (2008)
This dissertation presents a brief introduction to the semiconductor industry and elaborates the implementation of a typical optical character recognition (OCR) module on one particular processing type of semiconductor processing tool, namely the etching tool. The OCR module was implemented to assist the semiconductor wafer fabrication (Fab) to perform wafer tracking in the factory, which can help to speed up the process of finding a process problem down the line.